//================================= // Created on: 2018/11/09 21:30:39 //================================= #include #define show(x) std::cerr << #x << " = " << (x) << std::endl using ll = __int128_t; std::istream& operator>>(std::istream& is, ll& v) { std::string s; is >> s, v = 0; for (std::size_t i = 0; i < s.size(); i++) { if (isdigit(s[i])) { v = v * 10 + s[i] - '0'; } } if (s[0] == '-') { v *= -1; } return is; } std::ostream& operator<<(std::ostream& os, const ll& v) { if (v == 0) { return (os << "0"); } __int128_t num = v; if (v < 0) { os << '-', num = -num; } std::string s; for (; num > 0; num /= 10) { s.push_back((char)(num % 10) + '0'); } reverse(s.begin(), s.end()); return (os << s); } template std::ostream& operator<<(std::ostream& os, const std::vector& v) { os << "["; for (const auto& p : v) { os << p << ","; } return (os << "]\n"); } int main() { long long P; int Q; std::cin >> P >> Q; constexpr ll SQRT = 32000; std::vector f(SQRT + 1, 0); for (ll i = 1; i <= SQRT; i++) { f[i] = P % i; } for (int i = 1; i <= SQRT; i++) { f[i] += f[i - 1]; } std::vector r, s, t, b; for (ll i = SQRT; i >= 1; i--) { const ll S = P / (i + 1) + 1; const ll T = P / i; if (T >= S) { r.push_back(i), s.push_back(S), t.push_back(T); const ll sum = (2 * P - i * (S + T)) * (T - S + 1) / 2; b.push_back(sum); } } s.push_back(P + 1); for (int i = 1; i < b.size(); i++) { b[i] += b[i - 1]; } for (int q = 0; q < Q; q++) { long long L, R; std::cin >> L >> R; if (R <= SQRT) { std::cout << f[R] - f[L - 1] << std::endl; } else if (L > P) { std::cout << (R - L + 1) * P << std::endl; } else { ll ans = (L > SQRT) ? 0 : f[SQRT] - f[L - 1]; ans += (R > P) ? (R - P) * P : 0; if (R > P) { R = P; } if (L <= SQRT) { L = SQRT + 1; } const ll lind = std::lower_bound(s.begin(), s.end(), L) - s.begin(); const ll rind = std::upper_bound(t.begin(), t.end(), R) - t.begin() - 1; if (rind >= lind) { ans += b[rind] - b[lind - 1]; } else if (lind - rind >= 2) { std::cout << (2 * P - (R + L)) * (R - L + 1) / 2 << std::endl; continue; } const ll T = t[lind - 1]; ll sum = (2 * P - r[lind - 1] * (L + T)) * (T - L + 1) / 2; ans += sum; const ll S = s[rind + 1]; sum = (2 * P - r[rind + 1] * (S + R)) * (R - S + 1) / 2; ans += sum; std::cout << ans << std::endl; } } return 0; }